Developing strategic writers through genre instruction resources for grades 3-5 - Philippakos, Zoi A.; MacArthur, Charles A.; Coker, David L. Jr (The Guilford Press, 2015)
"The Common Core State Standards (CCSS) identify three essential writing genres--narrative, persuasive, and informative. This highly practical guide offers a systematic approach to instruction in each genre, including ready-to-use lesson plans for grades 3-5. Grounded in research on strategy instruction and self-regulated learning, the book shows how to teach students explicit strategies for planning, drafting, evaluating, revising, editing, and publishing their writing. Sixty-four reproducible planning forms and student handouts are provided in a convenient large-size format; purchasers also get access to a Web page where they can download and print the reproducible materials. The Appendix contains a Study Guide to support professional learning"--Provided by publisher.